PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK INDIHOME DI PT.TELKOM INDONESIA KEDIRI - Kurniawan, Luvi; Samari; Ratnanto, Sigit (Universitas Nusantara PGRI Kediri, 2022)
This have a look at to decide the extent purchasing decisions by analyzing factors that influence the level of purchasing decisions including products, prices and indihome promotions in the city of Kediri. This research methodology uses quantitative methods conducted using data collection techniques. observation and Distribute questionnaires. sampling and research using non-probabability sampling. The population of this study is all consumers PT. Telkom in Bandar Lor, Mojoroto, Kediri City, the number of which is not limited or unknown. The sample used 40 respondents by using purpososive sampling technique. Data collection method using questionnaires which was then analyzed using SPSS software for windows version 25. The analysis used The study was a validity test, a reliability test, a classical hypothesis test and a multiple linear regression test, coefficient determination (R2), T test, F test. Results research shows Product quality matters influence on indihome purchasing decisions, promotions do not have a significant influence on indihome purchasing decisions